Diurnal Variation of 8-hydroxy-2’-deoxyguanosine in Continuous Time Series of Two Breast Cancer Survivors - Joschua Geuter; Lennart Seizer; Germaine Cornelissen Guillaume; Ayse Basak Engin; Dietmar Fuchs; Christian Schubert (Journal of Circadian Rhythms)
8-hydroxy-2’deoxyguanosine (8-OHdG) is an oxidative product removed from DNA following radical oxygen species-induced damage. As a water-soluble molecule, it can be measured non-invasively in urine and is commonly used as a marker for ‘whole-body’ oxidative stress. However, its validity and reliability in assessing oxidative stress across various chronic diseases and in early carcinogenesis screening in clinical diagnosis and research remain subjects of debate. To determine optimal measurement timing and duration, it is essential to establish the circadian profile of 8-OHdG under everyday life conditions. Here, applying the integrative single-case design, we show the presence of day-night differences for 8-OHdG in continuous time series of two breast cancer survivors while considering different correction approaches. The participants sampled their urine in 12-h-pooled collections over one month. In both subjects, 8-OHdG levels were significantly higher during the day than at night regardless of whether they were corrected by creatinine or urine volume (creatinine corrected: t = –6.43, p < 0.01 [subject 1], t = –2.69, p = 0.01 [subject 2]; volume corrected: t = –7.30, p < 0.01 [subject 1], t = –3.69, p < 0.01 [subject 2]). Notably, urinary 8-OHdG levels show higher variability in night samples compared to day samples. These findings underscore the importance of considering daily fluctuations in 8-OHdG levels in both clinical and research studies, as well as the need to account for the dynamic characteristics of stress markers to minimize the risk of inconsistent or misleading results in clinical diagnostics.